A Deterministic and Statistical Energy Analysis of Tyre Cavity Resonance Noise - Zamri, Mohamed; Wang, Xu (Elsevier Ltd, 2016)
Tyre cavity resonance was studied using a combination of deterministic analysis and statistical energy analysis where its deterministic part was implemented using the impedance compact mobility matrix method and its statistical part was done by the statistical energy analysis method. While the impedance compact mobility matrix method can offer a deterministic solution to the cavity pressure response and the compliant wall vibration velocity response in the low frequency range, the statistical energy analysis method can offer a statistical solution of the responses in the high frequency range. In the mid frequency range, a combination of the statistical energy analysis and deterministic analysis methods can identify system coupling characteristics. Both methods have been compared to those from commercial softwares in order to validate the results. The combined analysis result has been verified by the measurement result from a tyre-cavity physical model. The analysis method developed in this study can be applied to other similar toroidal shape structural-acoustic systems.